2023
DOI: 10.1038/s41598-023-33550-z
|View full text |Cite|
|
Sign up to set email alerts
|

Full characterization of superradiant pulses generated from a free-electron laser oscillator

Abstract: The detailed structure of superradiant pulses generated from a free-electron laser (FEL) oscillator was experimentally revealed for the first time. Owing to the phase retrieval with a combination of linear and nonlinear autocorrelation measurements, we successfully reconstructed the temporal waveform of an FEL pulse including its phase variation. The waveform clearly exhibits the features of a superradiant pulse, the main pulse followed by a train of sub-pulses with π-phase jumps, reflecting the physics of lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This upgrade enabled an increase in the extraction efficiency of KU-FEL from 5.5% to 9.4%, which is a record-high extraction efficiency [12]. Under the photocathode operation of the 4.5-cell RF gun, it was confirmed that the FEL micro-pulse energy and duration were ~100 µJ [12] and 150 fs (4.2 cycles at 10.7 µm), respectively [13]. The other upgrade was the introduction of a new photocathode RF gun dedicated to the generation of electron beams, with a bunch charge of 1 nC or even higher because of the available electron-bunch charge of the 4.5-cell RF gun being limited to ~200 pC due to the small cathode size (2 mm in diameter), the small inter-cavity irises (8 mm in diameter), the low on-cathode electric field (<30 MV/m), and the absence of a focusing solenoid.…”
Section: Introductionmentioning
confidence: 88%
“…This upgrade enabled an increase in the extraction efficiency of KU-FEL from 5.5% to 9.4%, which is a record-high extraction efficiency [12]. Under the photocathode operation of the 4.5-cell RF gun, it was confirmed that the FEL micro-pulse energy and duration were ~100 µJ [12] and 150 fs (4.2 cycles at 10.7 µm), respectively [13]. The other upgrade was the introduction of a new photocathode RF gun dedicated to the generation of electron beams, with a bunch charge of 1 nC or even higher because of the available electron-bunch charge of the 4.5-cell RF gun being limited to ~200 pC due to the small cathode size (2 mm in diameter), the small inter-cavity irises (8 mm in diameter), the low on-cathode electric field (<30 MV/m), and the absence of a focusing solenoid.…”
Section: Introductionmentioning
confidence: 88%
“…Consequently, the pulse duration was evaluated as 150 fs, corresponding to 4.2 optical field cycles. 19) The LEBRA FEL is an IR light source covering wavelengths from 1 to 6 μm. [20][21][22] This range overlaps well with the solid-state lasers widely used for HHG investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Interferometric first-order and SHG simultaneous autocorrelation measurements are valuable because they allow the reconstruction of a pulse shape by retrieving the spectral phase information. 19,25,26) However, it is sensitive to the alignment accuracy of the optical system and takes much effort and time to adjust. Furthermore, the step size of the optical delay scanning of interferometric measurements should be one-tenth of the fundamental wavelength.…”
Section: Introductionmentioning
confidence: 99%